The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/anie.201708790
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Click and Release Reaction of Iminosydnones with Cycloalkynes

Abstract: We report the discovery of a new bioorthogonal click-and-release reaction involving iminosydnones and strained alkynes. This transformation leads to two products resulting from the ligation and fragmentation of iminosydnones under physiological conditions. Optimized iminosydnones were successfully used to design innovative cleavable linkers for protein modification, thus opening up new areas in the fields of drug release and target-fishing applications. This click-and-release technology offers the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 37 publications
0
77
0
2
Order By: Relevance
“…[76a] Bernard et al designed iminosydnones that, insteado fr eleasing CO 2 ,reacted with strained alkynes and, following cycloreversion, resulted in the formation of an acyl isocyanate;s aid isocyanate spontaneously hydrolyzed and underwent decarboxylation to release urea products. [77] Ar elated sydnone design enabled the controlled release of sulfonamides. [78] For the sydnones releasing ureas, the rate of the reactionw ith dibenzocyclooctyne was 3.15 m À1 s À1 in PBS/DMSO (4:1) at 25 8C; additional strain increasedt he reactionr ate further,a lbeit at the risk of decreasing the stability of the alkyne.…”
Section: Release Triggered By Strained Alkenes and Alkynesmentioning
confidence: 99%
“…[76a] Bernard et al designed iminosydnones that, insteado fr eleasing CO 2 ,reacted with strained alkynes and, following cycloreversion, resulted in the formation of an acyl isocyanate;s aid isocyanate spontaneously hydrolyzed and underwent decarboxylation to release urea products. [77] Ar elated sydnone design enabled the controlled release of sulfonamides. [78] For the sydnones releasing ureas, the rate of the reactionw ith dibenzocyclooctyne was 3.15 m À1 s À1 in PBS/DMSO (4:1) at 25 8C; additional strain increasedt he reactionr ate further,a lbeit at the risk of decreasing the stability of the alkyne.…”
Section: Release Triggered By Strained Alkenes and Alkynesmentioning
confidence: 99%
“…We and others have recently shown that sydnones can react in am etal-free strain-promoted click fashion with cyclooctyne reagents for the in vitro bioconjugation of purified proteins. [12][13][14][15][16] Herein, we report on the preparation and utilization of sialic acids bearing as ydnone reporter as novel metabolic precursors for the labeling of sialoconjugates in living cells ( Figure 1). We observed that while neuraminic acid modified at the 5-position with sydnone (Neu5SydCl) was not metabolically incorporated into sialosides,asialic acid analogue having the sydnone moiety at its 9-position (Neu9NSydCl) was well tolerated by the biosynthetic machinery of the cell, leading to robust display of the reporter on cell-surface sialoconjugates.I nterestingly,f urther in vitro enzymatic studies revealed that unlike CMP-Neu5Ac, CMP-Neu9-NSydCl is not au niversal donor substrate of all the STs involved in the synthesis of N-glycans,u ltimately leading to the favored incorporation of the reporter into linkage-specific a2,6-N-linked sialoproteins,abeneficial outcome,s ince MOE, while useful for reporting on global sialylation, is usually unable to differentiate among the various types of sialosides.…”
mentioning
confidence: 99%
“…In the process,afirst [3+ +2]-cycloaddition is followed by ar etro Diels-Alders tep generating ap yrazole "click" product and the concomitant release of the substituent connectedt ot he exocyclic nitrogen of the ImSyd structure. [11] This technology enabled the complete releaseo fafluorophore from an antibodyi nb loodp lasma and the full concomitant recovery and labelling of an immobilized protein under mild and physiological conditions. Am ajor advantage of this transformation compared to previous developments is the opportunity to use cyclooctyne derivatives which are commerciallya vailable or can easily be obtained from appropriate precursors.…”
mentioning
confidence: 99%
“…Thec arbonylation of 7c in presence of 15 mol %o f [PdCl 2 (PPh 3 ) 2 ], triethylamine (TEA) and EtOH delivered in 2.5 hours the desired ester 9e in 71 %y ield. [11] This optimized protocolt urned out to be the moste ffective to introduce a strong electron-withdrawing substituent on the N 3 position of the ImSyd scaffold, which cannot be otherwise obtained by the standard cyclization procedure (see Figure 1, compounds 4f,g). Finally,w ep roved that ImSyd 7c is ac ompetent substrate for Stille coupling:v inyl derivative 9g was synthetized using tributyl(vinyl)tin in 82 %y ield.…”
mentioning
confidence: 99%
See 1 more Smart Citation